Aged Cattle Brain Displays Alzheimer's Disease-Like Pathology and Promotes Brain Amyloidosis in a Transgenic Animal Model - Moreno-Gonzalez, Ines; Edwards, George; Morales, Rodrigo; Duran-Aniotz, Claudia; Escobedo, Gabriel; Marquez, Mercedes; Pumarola, Marti; Soto, Claudio (Frontiers in Aging Neuroscience, 2022)
Alzheimer's disease (AD) is one of the leading causes of dementia in late life. Although the cause of AD neurodegenerative changes is not fully understood, extensive evidence suggests that the misfolding, aggregation and cerebral accumulation of amyloid beta (Aβ) and tau proteins are hallmark events. Recent reports have shown that protein misfolding and aggregation can be induced by administration of small quantities of preformed aggregates, following a similar principle by which prion diseases can be transmitted by infection. In the past few years, many of the typical properties that characterize prions as infectious agents were also shown in Aβ aggregates. Interestingly, prion diseases affect not only humans, but also various species of mammals, and it has been demonstrated that infectious prions present in animal tissues, particularly cattle affected by bovine spongiform encephalopathy (BSE), can infect humans. It has been reported that protein deposits resembling Aβ amyloid plaques are present in the brain of several aged non-human mammals, including monkeys, bears, dogs, and cheetahs. In this study, we investigated the presence of Aβ aggregates in the brain of aged cattle, their similarities with the protein deposits observed in AD patients, and their capability to promote AD pathological features when intracerebrally inoculated into transgenic animal models of AD. Our data show that aged cattle can develop AD-like neuropathological abnormalities, including amyloid plaques, as studied histologically. Importantly, cow-derived aggregates accelerate Aβ amyloid deposition in the brain of AD transgenic animals. Surprisingly, the rate of induction produced by administration of the cattle material was substantially higher than induction produced by injection of similar amounts of human AD material. Our findings demonstrate that cows develop seeding-competent Aβ aggregates, similarly as observed in AD patients.